Polysemy of Linguistic Terms in English, Russian and Uzbek Languages - Dalieva Madina Khabibullaevna (International Journal on Integrated Education, 2022)
The article deals with the phenomenon of semantic derivation, analyzes various points from the point of view of this phenomenon, a slightly different interpretation of it and a method of analysis are proposed for polysemantic units. The object of this research is the English, Russian and Uzbek terminologies. The purpose of the article is to explore the concept of polysemy in the English, Russian and Uzbek language. To achieve this goal, we have made an attempt to study theoretical issues, to find examples of this phenomenon in English, Russian and Uzbek terminologies. The article provides a brief review of the interpretations and definitions of the concept of polysemy proposed by authoritative terminologists.